Acute Post-Exercise Oxygen Uptake, Hormone and Plasma Metabolite Response in Obese Men - Lanzi, S.; Codecasa, F.; Cornacchia, M.; Maestrini, S.; Salvadori, A.; Fanari, P.; Brunani, A.; Malatesta, D. (Hormone and Metabolic Research, 2014)
This study aimed to compare oxygen uptake (  V˙O2), hormone and plasma metabolite responses during the 30 min after submaximal incremental exercise (Incr) performed at the same relative/absolute exercise intensity and duration in lean (L) and obese (O) men. Eight L and 8 O men (BMI: 22.9±0.4; 37.2±1.8 kg · m−2) completed Incr and were then seated for 30 min.   V˙O2 was monitored during the first 10 min and from the 25–30th minutes of recovery. Blood samples were drawn for the determination of hormone (catecholamines, insulin) and plasma metabolite (NEFA, glycerol) concentrations. Excess post-exercise oxygen consumption (EPOC) magnitude during the first 10 min was similar in O and in L (3.5±0.4; 3.4±0.3 liters, respectively, p=0.86). When normalized to percent change (  V˙O2END=100%), %   V˙O2END during recovery was significantly higher from 90–120 s in O than in L (p≤0.04). There were no significant differences in catecholamines (p≥0.24), whereas insulin was significantly higher in O than in L during recovery (p=0.01). The time-course of glycerol was similar from 10–30 min of recovery (−42% for L; –41% for O, p=0.85), whereas significantly different patterns of NEFA were found from 10–30 min of recovery between groups (−18% for L; +8% for O, p=0.03). Despite similar EPOC, a difference in   V˙O2 modulation between groups was observed, likely due to faster initial rates of   V˙O2 decline in L than in O. The different patterns of NEFA between groups may suggest a lower NEFA reesterification during recovery in O, which was not involved in the rapid EPOC component.
Keywords: energy expenditure; physical activity; weight management; indirect calorimetry